Analysis of Traditional Art Content of The Dayak Ngaju Tribe “Karungut” as Strengthening the Emotional Social Education of Students in Palangka Raya - Prawati, Melinda; Sion, Holten; Fransiska, Carolina (IKIP PGRI Bojonegoro, 2025)
Education aims to optimally develop the human potential possessed by individuals. The art of